The Legal Aspects of the Use of the Electronic Fiscal and Customs Services Platform by Entrepreneurs Engaged in the International Trade of Goods (Ius Novum, 2025)
Entrepreneurs engaged in international trade are required to use the Electronic Fiscal and Customs Services Platform for the purpose of communicating with the National Tax Administration on matters relating to economic and tax policy. This modern technological tool plays an important role in the day-to-day operations of businesses and in the settlement of customs and other border taxes levied on economic operators engaged in the cross-border trade of goods within the European Union customs territory. The Electronic Fiscal and Customs Services Platform is an institution established under Polish law, aimed at implementing systemic, comprehensive solutions related to EU customs law. The objective of this article is to demonstrate that EU standards have been sufficiently detailed by the provisions of the Customs Law Act to ensure the functional implementation of this platform by Polish entrepreneurs. Without taking into account the specific circumstances of national legislation, electronic data-processing systems would be unable to function effectively within the context of the Polish economic framework.
Keywords: PUESC, custom, trade of goods, entrepreneur